Policy responses to complex environmental problems: insights from a science-policy activity on transboundary haze from vegetation fires in Southeast Asia - Murdiyarso, Daniel; Lebel, L.; Gintings, A.N.; Tampubolon, S.M.H.; Heile, A.; Wasson, M. (2004)
Transboundary pollution from vegetation fires is a recurrent and highly politicised environmental problem in Southeast Asia. This paper is a critical synthesis of the policy response to the severe haze episodes of 1997/1998. It is based on a series of science–policy activities co-ordinated by the Global Change Impacts Centre for Southeast Asia aimed at exploring land-use planning and management options to reduce the impacts of transboundary pollution from vegetation fires. We begin with a brief summary of what is known about the causes of the fires and haze, the composition and distribution of haze, and the main impacts. Policy options and instruments are considered at a range of levels, from local waste-wood management options and national land development strategies, through to regional and international institutions. In these analyses, we seek to understand the interaction of different interest groups and identify potentially complementary policies as well as likely tradeoffs. Ultimately, the aims of these activities are improvement of the public policy process and greater relevance of research activities and research-based knowledge.